The empowerment of the Nasyiatul Aisyiyah as parenting trainers for ‘Ibu Bakoh Keluarga Kokoh’ - Riana Mashar; Dwi Hastuti (Community Empowerment, 2021)
The role of post-disaster needs assessment cadres (PDNA) as a driver in motivating, assisting, and providing solutions for family resilience is increasingly needed during the pandemic. The purpose of this activity is to improve the technical skills of parenting trainers as they help families utilize social media-based smart parenting programs and increase cadre awareness in designing training according to the needs of family members. The method used to achieve this goal is the Participatory Rural Appraisal (PRA) approach. In the implementation stage of the service program, training activities to improve the soft skills and hard skills of cadres as parenting trainers were carried out through online and offline learning. The results of this activity revealed that the Ibu Bakoh Keluarga Kokoh training increased the motivation of PDNA administrators to contribute in solving parenting problems for members, increased the shared understanding of parenting skills, taught parents the role of social media as a psychoeducational parenting media and increased the confidence and skills of the parenting trainers.